2023
DOI: 10.1002/jpen.2499
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing transition from pediatric to adult care in short bowel syndrome and intestinal failure

Abstract: As the majority of children with short bowel syndrome (SBS) and intestinal failure (IF) are now surviving into adulthood, there is a paradigm shift from short‐term management to long‐term outcomes and a growing need to focus on healthcare transition (HCT). It is imperative that adolescents and young adults with SBS and IF receive disease education, empowerment, and support as they navigate the transition from pediatric to adult care. Furthermore, both pediatric and adult healthcare providers who manage these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(88 reference statements)
0
2
0
Order By: Relevance
“… 2 , 3 This study also reported a high incidence of anxiety and mood disorders in CHD. 1 Recognition of this problem led to the development of a 2-year fellowship in subspecialty care of adults with CHD, as it became clear that formalized physician training was needed to provide the best care for these patients. Kyrana et al 4 found in a survey study that one-third of responding practitioners noted “psychological problems” in their adolescent/young adult transition intestinal failure patients.…”
Section: Challenges For Transition To Adult Carementioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 This study also reported a high incidence of anxiety and mood disorders in CHD. 1 Recognition of this problem led to the development of a 2-year fellowship in subspecialty care of adults with CHD, as it became clear that formalized physician training was needed to provide the best care for these patients. Kyrana et al 4 found in a survey study that one-third of responding practitioners noted “psychological problems” in their adolescent/young adult transition intestinal failure patients.…”
Section: Challenges For Transition To Adult Carementioning
confidence: 99%
“…The transition of pediatric short bowel syndrome (SBS) patients to an adult gastroenterology (GI) practice presents substantial challenges to patients, their families, and their providers. 1 Although many of these challenges are shared by young patients with other chronic diseases, some are unique to the SBS patient population. There are few studies of the effect of transition on the long-term outcomes of pediatric SBS patients.…”
mentioning
confidence: 99%